Implicit Bias in Maternal Health: Racial Disparities in the District of Columbia, Maryland, and Virginia Area (DMV) (Georgetown Scientific Research Journal, 2026)
The United States has the highest maternal mortality rate among high-income countries, with disparities prevalent in the District of Columbia, Maryland, and Virginia metropolitan area (DMV). Black women experience disproportionately high rates of severe morbidity and death, persisting across socioeconomic levels, suggesting the role of implicit bias in shaping care. These biases manifest through inequitable use of interventions, stigmatized medical documentation, and dismissive provider-patient interactions, contributing to preventable adverse outcomes. Addressing these issues requires examining the presence of bias in both clinical encounters and the broader organizational, cultural, and policy contexts that perpetuate disparities. Efforts to address implicit bias must extend beyond one-time training and instead prioritize standardized protocols, workforce diversity, and structural reforms in education that lead to meaningful improvements in outcomes. Integrating policy initiatives would be a step towards reducing preventable maternal mortality among marginalized populations across the DMV.